Mirror foot: a case report of rare ten toes polydactyly - Sitorus, Gina Yunita J.; Putra, Teuku Nanda; Ikhsan, Muhammad; Jannah, Siti Miftahul (Journal of International Surgery and Clinical Medicine, 2023)
Introduction: A rare congenital deformity known as "mirror image polydactyly" of the feet is typified by symmetrical duplication of the foot's digits. According to one study, only 28 cases (seven of which have treatment records) have been described in the English-language literature. Mirror foot can arise as a single congenital defect or a component of a hereditary syndrome involving several congenital defects. In this study, we reported a mirror foot case and emphasized its rarity, unusual presentation, and successful surgical treatment. Case presentation: A 3-month-old female child was born with unilateral mirror image polydactyly of the foot with congenital talipes equinovarus (CTEV) and congenital genu recurvatum. She was referred to the outpatient clinic of the surgery department of dr. Kariadi General Hospital. In a radiological examination, ten digits and nine metatarsals were found on the left foot. Preaxial duplicates of the first to fourth metatarsals were disarticulated, followed by ablation of five digits. The aim of surgical management for this case was to reconstruct a functional and cosmetically pleasing foot, which will benefit orthopedic surgeons in managing CTEV for serial cast correction. Six months after surgical intervention, the foot showed a satisfactory appearance. However, management of the CTEV was uneventful at the local orthopedic department, and the patient was referred to the pediatric orthopedic center in Jakarta. Conclusion: Incidence of mirror foot is extremely rare, and treatment must be tailored to each individual. Coordination among different departments should be pursued to ensure optimum care for patients.